2012
DOI: 10.4103/0019-5413.96387
|View full text |Cite
|
Sign up to set email alerts
|

Total hip arthroplasty for failed aseptic Austin Moore prosthesis

Abstract: Background:Though Austin Moore (AM) replacement prosthesis has fairly good short term results for intracapsular femoral neck fractures in the elderly, it still is a compromised option and has a high failure rate in the long run. The objective of the present retrospective study is to analyze the functional outcome, assess survivorship of revision total hip arthroplasty (THA) at mid to long term followup, and evaluate intraoperative difficulties faced during conversion of failed aseptic AM prosthesis to cemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Austin-Moore HA had been selectively used for elderly patients with femoral neck fractures [39]. However, a poor quality of life and unsatisfactory results reportedly affect as many as 48% of physically active elderly patients [8]. The reported percentage of prosthesis survival ranges from 2% to 10% at mid-term follow-up and from 6% to 35% at long-term follow-up [10–15].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Austin-Moore HA had been selectively used for elderly patients with femoral neck fractures [39]. However, a poor quality of life and unsatisfactory results reportedly affect as many as 48% of physically active elderly patients [8]. The reported percentage of prosthesis survival ranges from 2% to 10% at mid-term follow-up and from 6% to 35% at long-term follow-up [10–15].…”
Section: Discussionmentioning
confidence: 99%
“…Grosso et al [21] reviewed the best available evidence in the literature and concluded that a cemented, unipolar HA should be reserved for low-demand elderly patients. However, the relatively low cost and good short-term outcomes have resulted in widespread use in inappropriate patients [7, 8]. With increasing life span and activity, the number of failed Austin-Moore HA procedures is increasing [69].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations